2018
DOI: 10.1021/acsomega.8b02514
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cell Detachment from Temperature-Responsive Poly(N-isopropylacrylamide-co-acrylamide)-Grafted Culture Surfaces by Spin Coating

Abstract: Poly(N-isopropylacrylamide-co-acrylamide) (PNIAM-co-AM)grafted surfaces have been reported to promote cell adhesion and detachment by a hydrophobic-to-hydrophilic transition triggered by temperature change. However, the surface uniformity and cell detachment consistency are still an issue. In this study, PNIAM-co-AM is prepared with spin coating to control the grafting density and the thickness and to achieve better cell detachment. The atomic force microscopy results indicate that the surface becomes smoother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…To confirm the relationships obtained from the prediction model, random samples prepared with different UV irradiation times and spin‐coating speeds were measured for their grafting density and thickness. Our previous study showed that by increasing the UV exposure time, the grafting thickness increased, and by increasing the spin‐coating speed, the consistency of the film thickness was improved 39 . The grafting density–thickness model was used to predict the grafting density of the samples, prepared with six different conditions with known thickness.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the relationships obtained from the prediction model, random samples prepared with different UV irradiation times and spin‐coating speeds were measured for their grafting density and thickness. Our previous study showed that by increasing the UV exposure time, the grafting thickness increased, and by increasing the spin‐coating speed, the consistency of the film thickness was improved 39 . The grafting density–thickness model was used to predict the grafting density of the samples, prepared with six different conditions with known thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Biocompatibility of the copolymer is the most important feature to be used as a cell attachment substrate. Thus, the potential toxicity of PNIPAm-co -AAc-b -PS and PNIPAm-co -AAc-b -PS copolymers have been evaluated on RAW264.7 cell lines using in vitro MTT dye reduction assay (Fentahun Darge et al, 2021;Sakulaue et al, 2018). The toxicity of the copolymers was performed by quantifying the viability of cells treated with copolymers (PNIPAm-co -AAc-b -PS and PNIPAm-co -AAc-b -PS) for 24 h at a concentration range of 0.0005 to 5 mg/mL.…”
Section: Cytotoxicity Test (Mtt Assay)mentioning
confidence: 99%
“…Therefore, unlike the bare cytodex 3, thermosensitive coated cytodex 3 microcarriers showed spontaneous cell detachments with reducing temperature lower than LCST. This temperature induced cell detachment strategy might be essential to harvest adequate viable cells with preserved cell features and functionality that are mostly lost during enzymatic cell dissociation (Kim et al, 2020;Sakulaue et al, 2018).…”
Section: Characterization Of Pnipam-co-aam-b-ps Coated Microcarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakayama et al reported that a polyNIPAm-coated petri dish was used successfully to culture endothelial cells while the cells were able to detach from the polyNIPAm-coated petri dish when the culture temperature was lowered from 37 °C to 20 °C [ 10 ]. Similarly, Sakulaue et al found that mouse preosteoblast MC3T-E1 cells were able to detach from a poly( N -isopropylacrymide- co -acrylamide)-grafted culture surface upon reducing the culture temperature to 20 °C [ 11 ]. Furthermore, in a study by Capella et al [ 12 ], polyNIPAm films were shown to be biocompatible and non-cytotoxic to mouse predipocytes cells, human embryonic kidney cells (HEK293) and human lung carcinoma epithelial cells (A549).…”
Section: Introductionmentioning
confidence: 99%